Possibility Intuitionistic Fuzzy Soft Expert Set Theory and Its Application in Decision Making - Ganeshsree Selvachandran; Abdul Razak Salleh (International Journal of Mathematics and Mathematical Sciences)
We propose the theory of possibility intuitionistic fuzzy soft expert theory and define some related concepts pertaining to this notion as well as the basic operations on this concept, namely, the complement, union, intersection, AND, and OR. The basic properties and relevant laws pertaining to this concept such as De Morgan’s laws are proved. Lastly, a generalized algorithm is introduced and applied to the concept of possibility intuitionistic fuzzy soft expert sets in hypothetical decision making problem.